Analisis Pendekatan dalam Pengelolaan Kelas - Prastyo, Hari; Abror, Nur Sasi Rohmah Jannati (Institut Agama Islam Uluwiyah Mojokerto Indonesia, 2023)
The process of classroom management is important for anyone to know, especially a teacher who devotes himself to the world of education. Management activities or class management can be interpreted as the ability of the teacher or homeroom teacher to utilize the potential of the class in the form of providing the widest possible opportunity for each person to carry out creative and directed activities so that available time and funds can be used efficiently to carry out activities Class activities related to curriculum and student development. In this case, a teacher must be able to control class conditions with various approaches including authoritarian approaches, intimidation approaches, permissive approaches, prescription approaches, behavior change approaches, socio-emotional approaches, group approaches and eclectic or pluralistic approaches, so that the learning process can be carried out. as expected, so that the learning objectives can be achieved.